Resilient Factors in Students with Disabilities - Delgado, Gustavo Rafael Escobar; Meza, Anicia Katherine Tarazona; GarcÃƒÂa, Andy Einstein GarcÃƒÂa (International Research Journal of Management, IT & Social Sciences, 2018)
The research analyzes the relationship between factors of resilience and academic performance in disabled students studying at the Technical University of ManabÃ. It is a correlational descriptive study conducted with a population of 88 disabled students, of which two groups were selected, one with high academic performance and the other with low performance. A questionnaire was designed and applied to determine the level of quality of life and risk factors of adolescents. Resilience was measured with the SV-RES scale created for the Latin American population.